(untitled) (Journal of Sciences & Technology, 2020)
In this paper, the effects of inclined magnetic field and slip boundary condition on heat and mass transfer in a Cassonnanofluid over a stretching sheet is examined. Brownian motion and thermophoreiss with chemical reation were considered as a nanofluid model and the fluid is electrically conducting in the presence of applied an inclined magnetic field. The nonlinear partial differential equations are transformed to nonlinear ordinary differential equationsby using appropriate transformation, which is solved numerically using a spectral collocation method. The effects of some fluid parameters on velocity, temperature and nanoparticle concentration profiles are shown graphically. Enhancement of both temperature and nanoparticle concentration were observed when there is an increase in thermophoresis parameter and the increase in slip parameter result to decrease in the velocity of the fluid.Local skin friction coefficient, local Nusselt number, and Sherwood number are analysed through tabulated results in table 1and 2.